Stabilization of the Virulence Plasmid pSLT of Salmonella Typhimurium by Three Maintenance Systems and Its Evaluation by Using a New Stability Test - Lobato-Márquez, Damián; Molina-García, Laura; Moreno-Córdoba, Inma; García-del Portillo, Francisco; Díaz-Orejas, Ramón (Frontiers in Molecular Biosciences, 2016)
Certain Salmonella enterica serovars belonging to subspecies I carry low-copy-number virulence plasmids of variable size (50-90 kb). All of these plasmids share the spv operon, which is important for systemic infection. Virulence plasmids are present at low copy numbers. Few copies reduce metabolic burden but suppose a risk of plasmid loss during bacterial division. This drawback is counterbalanced by maintenance modules that ensure plasmid stability, including partition systems and toxin-antitoxin (TA) loci. The low-copy number virulence pSLT plasmid of Salmonella enterica serovar Typhimurium encodes three auxiliary maintenance systems: one partition system (parAB) and two TA systems (ccdABST and vapBC2ST). The TA module ccdABST has previously been shown to contribute to pSLT plasmid stability and vapBC2ST to bacterial virulence. Here we describe a novel assay to measure plasmid stability based on the selection of plasmid-free cells following elimination of plasmid-containing cells by ParE toxin, a DNA gyrase inhibitor. Using this new maintenance assay we confirmed a crucial role of parAB in pSLT maintenance. We also showed that vapBC2ST, in addition to contribute to bacterial virulence, is important for plasmid stability. We have previously shown that ccdABST encodes an inactive CcdBST toxin. Using our new stability assay we monitored the contribution to plasmid stability of a ccdABST variant containing a single mutation (R99W) that restores the toxicity of CcdBST. The “activation” of CcdBST(R99W) did not increase pSLT stability by ccdABST. In contrast, ccdABST behaves as a canonical type II TA system in terms of transcriptional regulation. Of interest, ccdABST was shown to control the expression of a polycistronic operon in the pSLT plasmid. Collectively, these results show that the contribution of the CcdBST toxin to pSLT plasmid stability may depend on its role as a co-repressor in coordination with CcdAST antitoxin more than on its toxic activity.